A locking compression plate as an external fixator for treating infected nonunion of the humeral diaphysis. Issue 1 (December 2016) - Xiao, Cong; Tang, Fan; Zhou, Yong; Zhang, Wenli; Luo, Yi; Duan, Hong; Tu, Chongqi
Abstract Background Infected nonunion of the humeral diaphysis is a challenging problem for orthopedic surgeons. This study aimed to evaluate the outcome of using a locking compression plate (LCP) as a definitive external fixator in the management of infected nonunion of the humeral diaphysis after failure of internal fixation. Methods We retrospectively reviewed a series of seven patients with infected nonunion of the humeral diaphysis treated with an LCP as an external fixator between June 2010 and August 2014. There were five males and two females, with an average age of 40.9 years. Six out of seven patients had been definitively diagnosed with infection due to known bacteria by germiculture. The clinical and radiographic outcomes were retrospectively evaluated. Results All patients were followed-up for a mean period of 26.3 months (range 12–48 months). All fractures obtained complete bone union, and the average time to bone union was 7.9 months (range 3.5–15 months). All infections were eventually resolved without any recurrence of deep infection. Pin tract infection was only seen in one case. Only one patient had transient radial nerve palsy after surgery for traction. The average shortening length of the affected upper limb was 3 cm (range 2–4 cm) compared with the contralateral limb. At the last follow-up, the average Disabilities of the Arm, Shoulder and Hand score of the involved limbs was 3.2 (range 0–13.4). All patients obtained excellent or good functional results, and returned to their original work. Conclusions The novel use of an LCP as a definitive external fixator was an effective method for treating infected nonunion of the humeral diaphysis. However, a large-scale prospective clinical study is still needed to verify these findings.